Quality reform in Malaysian higher education governance: “identity formation” or “knowledge shopping”? - Quddus, S. M. Abdul; Ahmad, Khairil Izamin (Routledge, 2016)
In line with its Vision 2020, Malaysia has been implementing a series of ‘quality’ reforms in its higher education sector (Sirat, 2010). For critics, these reforms are driven by an ideological shift from the idea that knowledge is a “public good” (Dzulkifli, 2011, p. 28). This study explores whether the use of ‘standards’ as governance forms would lead Malaysia towards “identity formation”, i.e. the creation of a culture-based knowledge society, or direct it towards “knowledge shopping”, i.e. the commodification of higher education. This article concludes that Malaysian higher education governance is more oriented towards “knowledge shopping” than “identity formation.”